"You Get What You Need": Early Results of BloodTrack System on Reducing Inefficiencies in Blood Product Allocation. (9th November 2022) - Hung, S; Woddor, N; Husami, S; Fernandez, X
Abstract: Introduction/Objective: The preparation of blood products allocated for massive transfusion protocol (MTP) activation and surgical cases consumes much time and energy of blood bank technologists. Often, these blood products are returned to the blood bank unused. Clinicians may activate the MTP preemptively to ensure the availability of blood products in case they are needed. Most blood products ordered for surgeries are placed on hold and not transfused. These returned units require additional inspections before they can be made available again. To reduce these inefficiencies, we implemented the BloodTrack [Haemonetics, Boston, MA] system, wherein blood products are stored in remote refrigerators and made available to clinicians near the patients' bedside. Besides safeguarding units placed on hold for surgeries, we hypothesized that BloodTrack would provide greater visibility of available products in the emergency department (ED), thus reducing the rate of preemptive MTP activations. Methods/Case Report: From March 2022 onwards, BloodTrack refrigerators with OnDemand software were active in the ED, operating room (OR), and two intensive care (ICU) units. We educated ED, OR, and ICU nurses on the appropriate use of BloodTrack. MTP activations were recorded from August 2021 to June 2022. Data on units allocated to OR patients by BloodTrack were collected from software-generated logs. Data on units allocated to OR patients by BloodTrack were collected from software-generated logs. Results (if a Case Study enter NA): Since its introduction in March, BloodTrack has dispensed 92 red blood cell units, which represents 12% of the total 766 units assigned. The remainder of 674 units were unused, and represent substantial savings in time otherwise spent re-instating them. Moreover, the rates of preemptive MTP activations trended downwards, from 28% (32/113) in the 7 months prior to implementation, to 13% (3/24) after implementation. Conclusion: In conclusion, our implementation of BloodTrack has led to reduced MTP activations, improved efficiency of our blood product allocation process, and developed interdisciplinary care team integration.